Characterization of Essential Oils from Seven Salvia Taxa from Greece with Chemometric Analysis - Spyridon Tziakas; Ekaterina-Michaela Tomou; Panagiota Fraskou; Katerina Goula; Konstantina Dimakopoulou; Helen Skaltsa (Agronomy)
Over the years, several studies have investigated the essential oils (EOs) of Salvia taxa, revealing significant chemical variability in their composition. The present study focused on the characterization of the EOs of seven Salvia taxa growing wild in Greece, namely S. aethiopis L., S. argentea L., and S. sclarea L. (Aethiopis section); S. officinalis L. subsp. officinalis and S. tomentosa Mill. (Eusphace section); S. verticillata L. subsp. verticillata (Hemisphace section); and S. amplexicaulis Lam. (Plethiosphace section). Chemometric analysis, including PCA, HCA, and a clustered heat map, were applied to identify possible relationships among the samples based on their constituents, chemical groups, and thujone contents. The analysis classified the samples into two distinct groups based on their chemical classes; Group I (Svert, Sarg, Sampl, and Sath) was characterized by the highest amounts of sesquiterpene hydrocarbons (42.7–88.0%), followed by oxygenated sesquiterpenes (6.7–41.6%) and monoterpenes (0–17.2%), while Group II (Soff, Stom, and SScl) showed the highest amounts of oxygenated monoterpenes (47–66.4%), followed by monoterpene hydrocarbons (4.9–22.7%), sesquiterpenes (3.2–15.3%), and oxygenated diterpenes (3.5–9.0%). Regarding thujone content, two major groups were detected. The first group comprised Sscl, Svert, Sarg, Sampl, and Sath while the second group comprised Soff and Stom (Subgenus Salvia/Section Eusphace), which exhibited the highest percentages of thujones. These findings provide a basis for further investigation into taxonomic studies of the Salvia genus.